Notes sur la géomorphologie d’une partie de la Côte de Beaupré - Sabourin, R.-J.-E. (Cahiers de géographie du Québec, 1962)
Relief features of interest to the geomorphologist are numerous in the Québec City district. Among the more striking are the fault-line scarps at Montmorency Falls and on the island of Orléans and the various Champlain sea terraces among which Goldthwait's « 110-foot » and « Micmac » terraces are particularly well developed. A possible pre-Pleistocene section of the Montmorency river channel bas been suggested but still remains to be definitely established.